Aspiring to Home : South Asians in America. - Mani, Bakirathi (Asian America., 2012)
What does it mean to belong? How are twenty-first-century diasporic subjects fashioning identities and communities that bind them together? Aspiring to Home examines these questions with a focus on immigrants from India, Pakistan, and Bangladesh. Advancing a theory of locality to explain the means through which immigrants of varying regional, religious, and linguistic backgrounds experience what it means to belong, Bakirathi Mani shows how ethnicity is produced through the relationship between domestic racial formations and global movements of class and capital. Aspiring to Home focuses on po.